Impact of salinity stress on the response of aloe vera from different breeders on coastal sand land - Aprilia Rennanti Lunnadiyah; Purwanto Edi; Suryanti Venty; Rahayu Muji (BIO Web of Conferences)
Climate change has led to increased salinity in coastal areas, which can inhibit plant growth. Aloe vera (Aloe vera L.), a drought-resistant CAM (Crassulacean Acid Metabolism) plant with high economic potential, has the ability to tolerate dry environments but requires further study regarding its ability to withstand salinity stress, especially in coastal sandy soils impacted by climate change. This study aims to analyze the effect of salinity stress on the growth and yield of aloe vera from different nurseries in coastal areas. The experiment was conducted in a greenhouse using a completely randomized design with two factors: nursery origin (Gunung Kidul, Bantul, Cilacap) and salinity levels (0, 5, 10, and 20 g NaCl/L). Results showed that salinity stress significantly affected plant growth and yield. Each increase in NaCl concentration reduced growth and yield. Seeds from the Gunung Kidul nursery produced the best results in terms of plant height, number of leaves, leaf area, and fresh leaf weight. The best treatment interaction was found in the Gunung Kidul nursery without NaCl addition, with a leaf area reaching 18,006 cm2.